Geopositioning and Mobility. - Nait-Sidi-Moh, Ahmed (ISTE., 2013)
This book presents a general overview of the applications and use of geopositioning and GNSS for assisting the supervision and management of mobile terrestrial professions, information, traffic regulation, multimodal information, pedestrian mobility and indoor geopositioning, etc. It especially focuses on the field of mobility and terrestrial transport, the automotive industry and tourism (on foot, by bicycle or motorcycle, by car, by professional vehicles or by public transport, etc.). This book explores the many possibilities, developmental and organizational factors, as well as new.